2020
DOI: 10.1109/access.2020.2977455
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Evolution of the Integrity Methods Applied in GNSS

Abstract: The use of GNSS technologies has been spreading over time up to a point in which a huge diversity of applications require their use. Due to this demand, GNSS has turned into a more reliable technology, as multiple aspects of it have evolved. Integrity has become a vital aspect of being considered when using GNSS. The following document gathers and shows different aspects of integrity in terms of GNSS. The paper mainly focuses on the description of different receiver autonomous integrity monitoring methods. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…In the literature, a great variety of algorithms to evaluate a system’s integrity can be found that stem from different research areas [ 23 , 24 ]. Since the application in this work is in VDSE or localization functions, we focus in the following on approaches from the domain of navigation, especially localization functions based on a sensor fusion using a GNSS receiver, and adopt the nomenclature from this domain.…”
Section: State Of the Artmentioning
confidence: 99%
“…In the literature, a great variety of algorithms to evaluate a system’s integrity can be found that stem from different research areas [ 23 , 24 ]. Since the application in this work is in VDSE or localization functions, we focus in the following on approaches from the domain of navigation, especially localization functions based on a sensor fusion using a GNSS receiver, and adopt the nomenclature from this domain.…”
Section: State Of the Artmentioning
confidence: 99%
“…The integrity concept includes this second feature. It is defined as the measure of trust on the correctness of the location estimates applied to navigation systems [1]- [3].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of different FDE methods is provided by Zabalegui et al. (2020) and Knight and Wang (2009) (e.g., subset testing, sequential local test, forward‐backwards test, Danish method). J. Liu et al.…”
Section: Introductionmentioning
confidence: 99%